P55 The neurosurgical physician: a new role in the UK. Issue 3 (14th February 2019) - Stewart, PJ; Martin, J; Thomas, J; Hayhurst, C
Abstract : Objectives: With reduction in numbers of junior doctors and strict deanery requirements for training opportunities, the provision of ward cover and continuity has consistently fallen. Various methods of addressing this have been implemented in the UK, including increased nurse practitioners and physician associates. We introduced a new position of GP with a specialist neuroscience interest in line with the North American model of hospitalist and review the impact on patients and trainees. Design: Qualitative descriptive study. Subjects: 14 core and speciality trainees. Methods: Retrospective review of the impact of a permanent neurosurgical physician on ward care and provision of training with a qualitative study of trainee experience. Saturation was reached at 14 interviews. Results: A neurosurgical physician role was instituted in 2013, enabling a formal training rota to fulfil deanery requirements for core training and provide continuity of care at senior medical level, reducing medical ward consults to zero, improved communication with relatives and reduced the need for ST ward rounds. Qualitative assessment revealed a senior medical presence aided trainees own knowledge, resulted in better rapport and communication with patients and improved patient care through knowledge of best medical practice guidelines. Conclusions: The addition of the neurosurgical physician role has positively impacted on the quality of patient care and junior doctor training. Senior medical care is provided with continuity, in contrast to other models.